SPEECH ACCOMMODATION OF NON-NATIVE ENGLISH SPEAKERS IN ENGLISH SPEAKING COUNTRY: TEXTUAL ANALYSIS OF BAPSI SIDWA'S NOVEL "THE CROW EATERS" - Kayenat Shah; Muhammad Manzoor Alam; Laraib (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The role of communication within a culture is very vital. Culture is an important part of our thoughts; that's why we cannot separate ourselves from it. It is very necessary to understand culture and communication because both words are interconnected. In this paper, the researchers attempt to apply Giles's Communication accommodation theory to the situation where Jerbano, a non-native English speaker, tries to communicate with English speakers in London. The researchers analyze communication among non-native English speakers (Jerbano) with English speakers in London based on textual analysis. Bapsi Sidwa portrays the Parsi mind, social behavior, value systems, and custom in this novel. In the end, she explains the communication accommodation of non-native English speakers in an English-speaking country. She presents a typical story of a Parsi family and their social setting in her fictional novel. The novel "The Crow Eaters" by Bapsi Sidwa represents intercultural communication between the Parsi community and native English speakers of London. Bapsi Sidwa is a good social observer. In the novel, she demonstrates the communication barriers between non-native English speakers with native English speakers. Jerbano, a character in the novel, visited London with her family, where she tries her level best to accommodate her English speaking with native speakers of English.